Customer Satisfaction As An Indicator Of Educational Quality: A Study Of Quality Management In Madrasah - hafid, Ahmad Nur hafid; Siti Aimah (CV. Ulil Albab Corp, 2024)
This research aims to analyze customer satisfaction where students and parents are the main indicators in assessing the quality of education in madrasas, with a focus on the quality of teaching, educational facilities, and communication between madrasas and parents. Teaching quality includes teacher competence, effective learning methods, and the ability to convey material clearly, especially in Islamic religious education. Apart from that, teacher interaction with students and parent involvement in the educational process are also important factors that influence satisfaction. Through a qualitative approach with the case study method, data was collected through in-depth interviews with students, parents and teachers at selected madrasas. The research results show that teaching quality is the key element that most influences customer satisfaction. Teachers who are competent not only in academic aspects but also in providing moral and spiritual guidance are highly valued by students and parents. In addition, adequate educational facilities and open communication between madrasas and parents also contribute to increased satisfaction. This research found that feedback from customers (students and parents) is important in developing sustainable madrasah quality management. The results of this research provide recommendations for madrasas to continue to improve teacher competency through training and professional development, as well as improving educational facilities and strengthening communication with parents. In this way, madrasas can continue to be relevant and competitive in meeting the demands of educational modernization without ignoring Islamic identity.